2008
DOI: 10.1158/0008-5472.can-07-3195
|View full text |Cite
|
Sign up to set email alerts
|

Enzastaurin, a Protein Kinase Cβ Inhibitor, Suppresses Signaling through the Ribosomal S6 Kinase and Bad Pathways and Induces Apoptosis in Human Gastric Cancer Cells

Abstract: Activation of protein kinase C (PKC) has been implicated in gastric carcinogenesis. Enzastaurin is an oral ATP-competitive inhibitor of the PKCB isozyme. Although enzastaurin was initially advanced to the clinic based on its antiangiogenic activity, it is also known to have a direct effect on a variety of human cancer cells, inducing apoptosis by inhibiting the Akt signal pathway. However, data on enzastaurin for gastric cancer are limited. Therefore, this study was performed to assess the antitumor activity o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 27 publications
3
56
1
Order By: Relevance
“…Thus, when combining these two agents, enzastaurin can facilitate pemetrexed-damaged cells to undergo apoptosis. In line with our observations, previous studies showed little effects of enzastaurin alone on cell cycle progression (Lee et al, 2008), but others reported that the non-selective PKC inhibitor UCN-01 was able to inhibit the phosphorylation of Cdc25C and abrogate the G2/M checkpoint, potentiating the cytotoxicity of a variety of anticancer agents (Yu et al, 1998;Graves et al, 2000). However, enzastaurin was also able to influence other proteins involved in cell cycle regulation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, when combining these two agents, enzastaurin can facilitate pemetrexed-damaged cells to undergo apoptosis. In line with our observations, previous studies showed little effects of enzastaurin alone on cell cycle progression (Lee et al, 2008), but others reported that the non-selective PKC inhibitor UCN-01 was able to inhibit the phosphorylation of Cdc25C and abrogate the G2/M checkpoint, potentiating the cytotoxicity of a variety of anticancer agents (Yu et al, 1998;Graves et al, 2000). However, enzastaurin was also able to influence other proteins involved in cell cycle regulation.…”
Section: Discussionsupporting
confidence: 91%
“…Enzastaurin was originally evaluated in human tumour xenograft-bearing mice for its antiangiogenic activity upon PKCb inhibition, as it showed reduction of plasma VEGF levels together with a significant decrease in intratumoural vessel density (Keyes et al, 2004). However, several studies have shown that enzastaurin exhibits direct growth inhibiting effects on a wide array of cultured human tumour cells (Graff et al, 2005;Oberschmidt et al, 2005;Querfeld et al, 2006;Rizvi et al, 2006;Podar et al, 2007;Spalding et al, 2007;Lee et al, 2008). Recent studies suggest that the antitumour effects of enzastaurin are mediated through interference with the phosphatidylinositol 3-kinase (PI3K)/Akt pathway (Graff et al, 2005;Querfeld et al, 2006;Rizvi et al, 2006;Lee et al, 2008), an important pathway regulating the apoptotic response.…”
mentioning
confidence: 99%
“…However, we did not observe antiproliferative or toxic effects of enzastaurin on IL-2-stimulated NK cells at therapeutic relevant concentrations ranging from 0.625 µM to 2.5 µM. Notably, enzastaurin concentrations higher than 2.5 µM were required to affect cell proliferation and viability of some tumour cell types with highly activated PKCß [38,40]. However, enzastaurin concentrations between 0.625 µM and 2.5 µM inhibited dose-dependently GSK3ß phosphorylation in NK cells indicating an uncoupling of anti-proliferative effects of enzastaurin from effects on GSK3ß signalling.…”
Section: Page 16 Of 39contrasting
confidence: 61%
“…Enzastaurin has been reported to induce apoptosis in several tumors by interfering with signaling through the PI3K/AKT pathway [1,37,38]. We investigated by western blot the influence of enzastaurin on AKT activity and its downstream effectors in NK cells.…”
Section: Enzastaurin Directly Suppresses Gsk-3β (Ser 9 ) Phosphorylationmentioning
confidence: 99%
“…Enzastaurin induces apoptosis in a wide variety of human cancer cell lines including glioblastoma multiforme (1, 28), cutaneous T-cell lymphoma (29), colon (1), gastric (30), multiple myeloma (31,32), and Waldenstrom's macroglobulinemia (33). Our data indicate that enzastaurin treatment blocks 4E-BP1 phosphorylation and increases the association of eIF4E with 4E-BP1.…”
Section: Reducing 4e-bp1 Expression Suppresses Enzastaurin-induced Apmentioning
confidence: 72%